Carbon Tax : Renewing the Climate Policy of the EU by Shifting Taxation from Good to Bad - Correa De Mora, Anna (My University, 2021)
The taxation of CO2 emissions, the so-called carbon tax, is a topic that frequently arises in discussion surrounding the climate measures of the EU. The introduction of a harmonised carbon tax is considered an agile means of supplementing the climate change policies of the EU, given the presumed efficiency and effectiveness of a tax instrument. What the discussion lacks, however, is a construction of the legal requirements, the fulfilment of which precedes the implementation of a harmonised carbon tax. Although the competences of the EU could be deemed extensive in the field of environmental protection, said comprehensiveness does not apply to fiscal matters. The purpose of this thesis is to examine the requirements and expediency of a harmonised carbon tax in the EU by utilising regulatory theory. The topic is approached from three viewpoints. First, the policy objectives and regulatory standards common to environmental taxes are examined. The purpose of this approach is to outline the theoretical design of the harmonised tax. Second, the compatibility of a carbon tax with an emissions trading scheme is evaluated, because if carbon taxation were to be harmonised in the EU, the impact of such a measure on the emissions trading scheme of the EU could not be dismissed. Lastly, the legality of a harmonised carbon tax is analysed considering the general principles of EU law. It is found that should harmonisation of carbon taxation be pursued, the purpose thereof should not be the reduction of emissions per se but rather the renewal of the tax base composition of the Member States by shifting taxation to carbon intensive emission sources from those of labour and capital income. Notwithstanding, promoting said renewal by the means of secondary EU law is found to be inconsistent with the reviewed general principles of the EU. It is thus concluded that any coordination of carbon taxation should be undertaken by the Member States on a voluntary basis rather than by passing binding EU law.

Hiilidioksidipäästöjen verotus, eli niin kutsuttu hiilivero, on aihe, joka nousee ajoittain esiin EU:n ilmastotoimia koskevassa keskustelussa. Johtuen veroinstrumenttien oletetusta tehokkuudesta ja vaikuttavuudesta, hiiliveron käyttöönottoa pidetään etevänä keinona täydentää EU:n ilmasto-oikeudellista ohjauskeinovalikoimaa. Hiiliveroa koskevasta keskustelusta puuttuu kuitenkin ymmärrys harmonisoidun hiiliveron oikeudellisista edellytyksistä. Vaikka EU:n toimivalta ympäristönsuojelua koskevissa asioissa onkin kattava, ei vastaavaa toimivaltaa ole verotuksessa. Tämän tutkielman tarkoituksena on sääntelyteoriaa hyödyntämällä arvioida harmonisoidun hiiliveron edellytyksiä ja tarkoituksenmukaisuutta EU:ssa. Tutkielman aihetta lähestytään kolmesta näkökulmasta. Ensimmäiseksi tarkastellaan ympäristöveroille ominaisia ohjauskeinotavoitteita ja sääntelystandardeja. Tämän lähestymistavan tarkoituksena on hahmottaa harmonisoidun hiiliveron teoreettinen kehikko. Toiseksi arvioidaan hiiliveron yhteensopivuutta päästökauppajärjestelmän kanssa, sillä harmonisoidun hiiliverotuksen vaikutusta EU:n päästökauppajärjestelmään ei voitaisi sivuuttaa. Viimeiseksi tarkastellaan harmonisoidun hiiliveron lainmukaisuutta EU:n yleisten periaatteiden näkökulmasta. Tutkielman tarkastelu osoittaa, että harmonisoidun hiiliveron tarkoituksena ei tulisi olla päästöjen vähentäminen itsessään, vaan jäsenmaiden veropohjien uudistaminen siirtämällä verotuksen painopistettä ansio- ja pääomatulon verotuksesta hiili-intensiivisten päästölähteiden verotukseen. Toisaalta tutkielma osoittaa myös sen, että jäsenvaltioiden veropohjien uudistaminen EU:n sekundäärioikeudella olisi ristiriidassa tutkielmassa arvioitujen EU:n yleisten periaatteiden kanssa. Tästä syystä kansallisten hiiliverojen koordinointia tulisi edistää EU:n sitovan lainsäädännön sijasta jäsenvaltioiden vapaaehtoisilla toimilla.
Keywords: carbon tax, climate law, environmental law, EU law, tax law